Source of and potential bio-indicator for the heavy metal pollution in Ny-Ålesund, Arctic - Xiaofei, Wang; Linxi, Yuan; Honghao, Luo; Nanye, Long; Yuhong, Wang; Liguang, Sun (Polar Research Institute of China - PRIC, 2007)
Three kinds of tundra plant samples including Dicranum angustum (a type of boreal bryophyte), Puccinellia phryganodes (a type of fringy plant), Salix polaris (a type of vascular plant) and surface soil were samples in 200 at Ny-Ålesund of the Arctic. The levels of eight heavymetal elements (Hg, Pb, Cd, Cu, Zn, Ni, Fe and Mn) and three metal-like elements (As, Se, Sr) in the plant and soil samples of the areas within previous coal mining activities are significantly higher than those of other areas. The relative accumulation of these elements in these tundra plant samples is consistent with the one in the soil samples, especially in the areas affected by previous coal mining activities. Thus, the pollution is apparently from local coal mining activity. Dicranum angustum has the highest concentrations among those elements, and it can be a good bio-indicator for heavy metal pollution in Ny-Ålesund. Though Ny-Ålesund is less polluted by heavy metal than nearby Northern European human living areas, but much more than the tundras of the Alaska, Greenland and the Antarctic.